Application of Thermography In Ukraine - Venger, Ye.F.; Gordienko, V.I.; Dunaevskiy, V.I.; Kotovskiy, V.I.; Maslov, V.P. (Science and Innovation, 2024)
The review presents the results of applying the thermography to the diagnosis of tumors, vertebral pain of athletes, vascular lesions, joint trauma, maxillofacial pathology, the study of battery pathogenic effect mechanisms in biologically active environment, the study of heterogeneity of thermal fields in newborn incubators, and to the simulation of pollutant propagation in ecology. On the basis of Ukrainian R&D the domestic industry has ensured the production of thermal imaging devices for military purposes. Wide application of thermal imaging thermography in Ukraine gives cause for anticipating a comprehensive development of this direction.